Kesesuaian Pasal 108 KHI Tentang Wasiat Perwalian Anak Kepada Badan Hukum dengan Hukum Islam - Mochammad Charitsal Chubba (AL-HUKAMA, 2018)
This is a bibliographical research that analyzes the appropriateness of article 108 of KHI (Islamic Law Compilation) concerning child trusteeship testament to legal entities with testamentary theories in Islamic law. In term of its formulation, it is known that article 108 of KHI does not have a basis and it contradicts the rules of Islamic law that exist according to the Shafi'i school of thought. In this case, there are two elements that are not in accordance with the rules of will in Islamic law, namely legal entities as recipient of will and guardianship as inherited object. It is because the legal entities are not individual recipient but an association consisting of several people who are not associated to religion and culture. In addition, the article is only based on a number of articles contained in the Civil Code and other laws, without detailed explanations regarding the articles and procedures that must be carried out and across the norms in the community. The solution that can be taken is the need for regulations regarding the criteria of legal entities that are permitted to accept the will and their responsibilities. And there should be a change from the word trusteeship to a representative that has a limited role compared to guardianship.